PENGEMBANGAN BUKU KOMIK BERBASIS SOSIO SCIENTIFIC ISSUES UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Diana Fadilla; Awalina Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The level of student engagement is low and there is an urgent need to improve the quality of student learning at the elementary level. This research aims to improve the critical thinking skills of elementary school students in class V. This research uses Research and Development (R&D) with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, evaluation. Comic book media was declared